Human neuro-rights - Farinella, Favio; Gulyaeva, Elena Evgenyevna (REVISTA QUAESTIO IURIS, 2022)
Resumo The invasion of the rights to privacy and intimacy, a result of massiveness achieved by the new information and communication technologies, becomes today a greater threat with the possibility that third parties access our thoughts and manipulate our memory. Technology applied to neuroscience may make this possible in the near future. Although at present the legal regulation of the use of neurotechnologies seems unnecessary, the question becomes relevant when they are used to map and modify the activity of the human brain. The future possibilities of the use of neurotechnologies will affect not only our lifestyle, but the very nature of what we understand today as the human being. In this first article we present the intersections between neurotechnology and law, which generates a new field called Neuro-Law. Along the current legal disruption taking place, we describe the basic characteristics of the proposal to affirm entirely new human rights based on new technologies applied to Neuroscience. Keywords: human rights / neurotechnology / neuro-rights / legal disruption / NeuroLaw Resumen La invasión de los derechos a la privacidad e intimidad producto de la masividad lograda por las nuevas tecnologías de la información y la comunicación, deviene hoy una amenaza mayor frente a la posibilidad que terceros accedan a nuestros pensamientos y puedan manipular nuestra memoria. La tecnología aplicada a la neurociencia puede volver esto posible en un futuro cercano. Si bien al presente la regulación legal del uso de las neurotecnologías parece innecesaria, la cuestión cobra relevancia cuando son utilizadas para mapear y modificar la actividad del cerebro humano. Las posibilidades futuras del uso de neurotecnologías, afectarán no solo nuestro estilo de vida, sino la misma naturaleza de lo que hoy entendemos es el ser humano. En este primer artículo presentamos las intersecciones entre neurotecnología y derecho, generando un espacio llamado Neuroderecho. Frente a la disrupción jurídica en marcha, describimos las características básicas de la propuesta de afirmar nuevos derechos humanos fundados en las nuevas tecnologías aplicadas a la Neurociencia. Palabras clave: derechos humanos / neurotecnología / neuro-derechos / disrupción legal / Neuro Derecho